TCV experiments towards the development of a plasma exhaust solution. (12th September 2017) - Reimerdes, H.; Duval, B.P.; Harrison, J.R.; Labit, B.; Lipschultz, B.; Lunt, T.; Theiler, C.; Tsui, C.K.; Verhaegh, K.; Vijvers, W.A.J.; Boedo, J.A.; Calabro, G.; et al.
Abstract: Research towards a plasma exhaust solution for a fusion power plant aims at validating edge physics models, strengthening predictive capabilities and improving the divertor configuration. The TCV tokamak is extensively used to investigate the extent that geometric configuration modifications can affect plasma exhaust performance. Recent TCV experiments continue previous detachment studies of Ohmically heated L-mode plasmas in standard single-null configurations, benefitting from a range of improved diagnostic capabilities. Studies were extended to nitrogen seeding and an entire suite of alternative magnetic configurations, including flux flaring towards the target (X divertor), increasing the outer target radius (Super-X) and movement of a secondary x -point inside the vessel ( X -point target) as well as the entire range of snowflake configurations. Nitrogen seeding into a snowflake minus configuration demonstrated a regime with strong radiation in the large region between the two x -points, confirming EMC3-Eirene simulations, and opening a promising path towards highly radiating regimes with limited adverse effects on core performance.